PENGARUH LINGKUNGAN TEMAN SEBAYA TERHADAP MOTIVASI BELAJARIPS SISWA KELAS VII SMP NEGERI 40 PEKANBARU TAHUN AJARAN 2017/2018. - Susanti, Yosa; Sumarno, Sumarno; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the influence of peer environment on learning motivation in the subjects of social studies students of Class VII SMP Negeri 40 Pekanbaru. The population in this study are students of class VII SMP Negeri 40 Pekanbaru that is as many as 211 students and sample of 68 students. Data collection using questionnaire technique. The data analysis used is simple linear regression. The results showed that the peer environment had an effect on the students' learning motivation in the IPS Subject in Class VII of SMP Negeri 40 Pekanbaru, the influence was 0.668. Judging from the calculation of R2 (R Square Change) obtained a value of 0.281, meaning that the contribution of peer environment to student learning motivation of 28.1%.Keyword : Peer Environment, Leraning Motivation